PENGARUH EXPERIENTIAL MARKETING DAN STORE ATMOSPHERE TERHADAP LOYALITAS PELANGGAN (Studi Pada Pelanggan Equal Coffe Dau Malang) - M. Izzudin; N. Rachma; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTExperiential marketing and store atmosphere have an influence on customer loyalty. This study aims to determine the responses of respondents about Equal Coffe Dau Malang experiential marketing, store atmosphere and customer loyalty and to determine the effect of expereriential marketing and store atmosphere simultaneously and partially on Equal customers Coffe Dau Malang. This study uses the explanatory research method and the sampling technique uses the Slovin formula with an error rate of 10%. The number of samples taken is 97 which is the consumer of Equal Coffe Dau Malang. The data analysis technique used is the analysis of instrument test, classic assumption test, multiple linear regression, simultaneous hypothesis test F and partial hypothesis test t. Based on the results of the analysis it can be concluded that the responses of respondents about Equal Coffe experiential marketing, store atmosphere and customer loyalty are good. Simultaneously experiential marketing and store atmosphere significantly influence customer loyalty. Partially experiential marketing and store atmosphere significantly influence customer loyalty. From the results of the research that has been carried out there are several suggestions for Equal Coffe in order to maintain product packaging and compounding and presentation for customers and improve the arrangement of indoor and outdoor spaces and make Equal Coffe decorations more harmonious with the typical dishes of Nusantara coffee makers.             Keywords: experiential marketing, store atmosphere and customer loyality